High-Salt Intake Ameliorates Hyperglycemia and Insulin Resistance in WBN/Kob-Leprfa/fa Rats: A New Model of Type 2 Diabetes Mellitus - Yoshiichi Takagi; Taichi Sugimoto; Masaya Kobayashi; Mitsuyuki Shirai; Fumitoshi Asai (Journal of Diabetes Research)
High-salt intake is a major risk factor for developing hypertension in type 2 diabetes mellitus, but its effects on glucose homeostasis are controversial. We previously found that high-salt intake induces severe hypertension in WBN/Kob diabetic fatty (WBKDF) rats. In the present study, we examined the effects of a high-salt intake on glucose homeostasis in WBKDF rats. Male WBKDF rats and age-matched Wistar rats at 6 weeks of age were each divided into two groups and fed either a normal-sodium (NS, 0.26%) diet or high-sodium (HS, 8%) diet for 7 weeks. Systolic blood pressure and urine volume were increased in WBKDF-HS and Wistar-HS. Body weight gain and food consumption were comparable between NS and HS in both strains. Plasma and urine glucose levels were significantly increased in WBKDF-NS but not in WBKDF-HS. HOMA-IR in WBKDF-HS was significantly lower compared with that in WBKDF-NS. The high plasma adiponectin level in WBKDF-NS compared with that in Wistar-NS was further enhanced in WBKDF-HS. Glycogen deposits and fat droplets in the livers of WBKDF-HS were reduced compared with those of WBKDF-NS. The present study demonstrated that HS intake ameliorated hyperglycemia and insulin resistance in WBKDF rats, which may be due to increased plasma levels of adiponectin.